Neurological Abnormalities in Chinese Schizophrenic Patients - Raymond C. K. Chan; Eric Y. H. Chen (Behavioural Neurology)
Background: This study attempted to examine the prevalence and type of neurological signs in Chinese patients with schizophrenia.